Abdominal pseudocyst: a rare complication of ventriculoperitoneal shunt - Omar Al-Mahrouqi; Tariq Al-Saadi (Egyptian Journal of Neurosurgery, 2025)
Abstract Like any other surgical intervention, ventriculoperitoneal shunt (VPS) insertion is associated with multiple complications including bleeding, shunt infection, and shunt malfunction. Additionally, other complications involve the gastrointestinal tract, such as CSF pseudocyst or abdomen pseudocyst (APC) formation, have also been reported. The APC inhibits cerebrospinal fluid (CSF) absorption and causes shunt malfunction. Differential diagnosis might be difficult since APC can mimic other cystic abdominal diseases. This article aims to provide an updated review that summarize the most relevant findings available in the literature. This review can help clinicians in better understanding the clinical characteristics of this complication in order to develop a comprehensive approach that is associated with a lower incidence and recurrence rate of APC. Accurate history taking, precise clinical examination of signs and symptoms, abdominal imaging, and a high index of suspicion are key components of an APC diagnosis. Therefore, understanding predisposing factors and clinical features of such distinctive complication is essential for the adequate management of patients. Abdominal pseudocyst formation at the distal end of VPS can result in both features of shunt malfunction and abdominal signs and symptoms. Post-VPS APC, whenever suspected, should be assessed appropriately by imaging. The treatment of APC ranges from shunt removal and external drainage to various forms of shunt repositioning or conversion, and treatment decisions often depend on individual patient characteristics and surgeon preference.